Penerapan Model Visual, Auditori, Kinestetik untuk Meningkatkan Keterampilan Membaca Puisi Siswa Kelas IV SDN Bendungan 1 Kabupaten Sumedang - Sukmana, Vegyta Tresya Putri; Djuanda, Dadan; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
This research was conducted using a visual, auditory, kinesthetic (VAK) model. The problem is that students have difficulty reading poetry with proper pronunciation, intonation and expression. The reason for this problem is that the teacher considers reading poetry difficult and has never been taught. For this reason, the efforts made by researchers are applying visual, auditory, and kinesthetic models. This model facilitates the three learning styles that students have. The method used in this study is class action research and consists of three cycle actions. Data from the research shows that poetry reading skills increase each cycle. In the first cycle results obtained at 50% of students completed, in the second cycle 65% of students completed and in the third cycle 90% of students declared complete. Thus, the visual, auditory, and kinesthetic models can improve students' poetry reading skills.Â